Same scandal, different moral judgments: the effects of consumer-firm affiliation on weighting transgressor-related information and post-scandal patronage intentions. (4th October 2021) - Lo, Carolyn Jia'En; Tsarenko, Yelena; Tojib, Dewi
Abstract : Purpose: Corporate scandals involving senior executives plague many businesses. Although customers and noncustomers may be exposed to news of the same scandal, they may appraise dimensions of the transgression differently, thereby affecting post-scandal patronage intentions. The purpose of this study is to investigate whether and how consumer-firm affiliation affects future patronage intentions by examining nuances in customers' vs noncustomers' reactions toward the transgressor's professional performance and immoral behavior. Design/methodology/approach: Four between-subjects experimental studies were used to test whether performance-relevant and/or immorality-relevant pathways drive customers' vs noncustomers' post-scandal patronage intentions. The results were analyzed using analysis of variance, parallel mediation and serial mediation. Findings: The results demonstrate that performance judgment, and not immorality judgment, drive the relationship between consumer-firm affiliation and post-scandal patronage intentions (Study 1a), regardless of the order of information presented (Study 1b). Customers form more positive performance judgments because they give more weight to performance-related information (Study 2), demonstrating a sequential effect of consumer-firm affiliation on post-scandal patronage intentions only through the performance-relevant, and not immorality-relevant, pathway (Study 3). Research limitations/implications: This research contributes to the literature on social distance and moral judgments. Future research should examine other deleterious outcomes such as brand sabotage and negative word-of-mouth, as well as potential moderators including repeated transgressions and prevalence of the infraction in other firms. Practical implications: This research offers important nuances for understanding how performance and immorality judgments differentially operate and affect post-scandal patronage intentions. The findings highlight the strategic value of communicating the leader's performance (e.g. professional contributions) as a buffer against potential declining patronage. Originality/value: Offering new insights into the extant literature and lay beliefs which contend that harsh moral judgment reduces patronage intentions, this research uncovers why and how exposure to the same scandal can result in varying moral judgments that subsequently influence patronage intentions. Importantly, this research shows that the performance-relevant pathway can explain why customers have higher post-scandal patronage intentions compared to noncustomers.